Biosynthesis of silver nanoparticles using cow dung extract and evaluation of their antibacterial potentials - Manoja Das; Dipti Kanta Acharya; Malati Hembrom; Ipsita Nayak (Microbes and Infectious Diseases, 2025)
Background:  Cow dung, also called cow pies or cow manure, is the excrement left behind by bovine animals, such as buffalo, yak, and cows.